Recombination between ccrC genes in a type V (5C2&5) staphylococcal cassette chromosome mec (SCCmec) of Staphylococcus aureus ST398 leads to conversion from methicillin resistance to methicillin susceptibility in vivo. - Chlebowicz, M. A.; Nganou, K.; Kozytska, S.; Arends, J. P.; Engelmann, S.; Grundmann, H.; Ohlsen, K.; van Dijl, J. M.; Buist, G. (Antimicrob Agents Chemother, 2010)
Various types of the staphylococcal cassette chromosome mec (SCCmec) are known to confer methicillin resistance on the human pathogen Staphylococcus aureus. Such cassettes are not always stably maintained. The present studies were aimed at identifying the mechanism underlying the in vivo conversion of methicillin-resistant S. aureus (MRSA) to methicillin-susceptible S. aureus (MSSA) derivatives as encountered in two patients suffering from pneumonia and an umbilicus infection, respectively. All MRSA and MSSA isolates identified belong to multilocus sequence type (MLST) 398, have spa type t034, and are Panton-Valentine leukocidin positive. Sequencing of 27,616 nucleotides from the chromosomal SCCmec insertion site in orfX to the hsdR gene for a restriction enzyme revealed a type V (5C2&5) SCCmec. Sequence comparisons show that parts of the cassette are highly similar to sequences within SCCmec elements from coagulase-negative staphylococci, indicating a possible common origin. The cassette investigated contains ccrC-carrying units on either side of its class C2b mec gene complex. In vivo loss of the mec gene complex was caused by recombination between the recombinase genes ccrC1 allele 8 and ccrC1 allele 10. In vitro, the SCCmec was very stable, and low-frequency MRSA-to-MSSA conversion was only observed when MRSA isolates were cultivated at 41 degrees C for prolonged periods of time. In this case also, loss of the mec complex was due to ccrC gene recombination. Interestingly, the MRSA and MSSA isolates studied displayed no detectable differences in competitive growth and virulence, suggesting that the presence of the intact type V (5C2&5) SCCmec has no negative bearing on staphylococcal fitness under the conditions used.
Keywords: Animals; Anti-Bacterial Agents/pharmacology; Bacterial Proteins/*genetics; Blotting, Southern; Electrophoresis, Gel, Pulsed-Field; Female; Methicillin/*pharmacology; Methicillin Resistance/*genetics; Mice; Mice, Inbred BALB C; Microbial Sensitivity Tests; Recombinases/*genetics; Recombination, Genetic/genetics/*physiology; Staphylococcal Infections/drug therapy/microbiology; Staphylococcus aureus/*drug effects/genetics/growth & development/*pathogenicity; Virulence/genetics